2015
DOI: 10.1111/1755-5922.12115
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Extended‐interval Follow‐up for Patients Receiving Warfarin

Abstract: Summary Aims The 2012 American College of Chest Physician Evidence‐Based Management of Anticoagulant Therapy guidelines suggest an international normalized ratio (INR) testing interval of up to 12 weeks, rather than every 4 weeks, for patients with consistently stable INRs while taking vitamin K antagonists. We aimed to examine the feasibility of extended‐interval follow‐up in a real‐world setting. Methods Patients receiving stable warfarin therapy for ≥12 weeks at baseline began extended‐interval follow‐up wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
(17 reference statements)
3
15
1
Order By: Relevance
“…While this was unexpected from our hypothesis given the prior warfarin dose stability of participants, it is consistent with prior literature that an increase in comorbidities can decrease INR stability [17,18]. Additionally, Carris et al found only 23% of participants able to receive 12-week INR follow-up intervals for a year [12].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…While this was unexpected from our hypothesis given the prior warfarin dose stability of participants, it is consistent with prior literature that an increase in comorbidities can decrease INR stability [17,18]. Additionally, Carris et al found only 23% of participants able to receive 12-week INR follow-up intervals for a year [12].…”
Section: Discussionsupporting
confidence: 90%
“…Our study advocates the use of a detailed protocol to safely extend the INR interval and offers guidance on longer-term use of an extended INR interval to complement what previous literature has described [12,13]. Our study found that by titrating the INR followup interval up to 12 weeks we could identify individuals who could not maintain an extended INR interval despite a previous history of warfarin dose stability.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…One other health system has published their experience with a similar de-implementation effort to reduce frequent INR tests among patients with stable warfarin control [16, 17]. However, they did not report on how frequently their staff scheduled the next INR test more than the standard 4 weeks into the future for eligible patients or the barriers and facilitators to their de-implementation effort.…”
Section: Discussionmentioning
confidence: 99%